THE FORM AND AFFECT OF AGORAPHOBIA TO ADOPT TO THE ENVIRONMENT IN THE NOVEL THE WOMAN IN THE WINDOW BY A. J. FINN - heldy yuliana; Siti Hafsah (Faculty of Letters Universitas Balikpapan, 2024)
This paper explores disability and the effect of Agoraphobia in the novel “The Woman in the Window”. There are two objectives of this research: 1) to identify disability of Agoraphobia of Anna Foxx in the novel “The Woman in the Window” and 2) to identify the effect of Agoraphobia to adopt to the environment in the novel “The Woman in the Window”. The theory used in this research is the Psychoanalysis using Sigmund Freud theory; the methodology employed is qualitative research in which researcher tried to present the issues descriptively. As for the data, they were collected from books, journal and internet. The novel were taken out as the primary data. This result of the research, the researchers finds that disability of Agoraphobia is nervous, panic attack and losing control and the effect of Agoraphobia to adopt to the environment are fear of going out, surrounding and lose.